Chemical Characterization of Silver Nanoparticle Compounds using Red Algae (Fucus vesiculosus) in Freeze Dry Methods - Savitri, Evika Sandi; Shinta; Eko Budi Minarno; Rahmi Annisa (The Journal of Experimental Life Science, 2023)
The nanoparticle green synthesis method is an alternative method for synthesizing nanoparticles or nanomaterials. The nanoparticle green synthesis method is a synthesis method that forms metal nanoparticles using natural materials such as plants as bioreductor. Red algae contain active ingredients that are the potential as antioxidants and anti-aging. Fucus vesiculosus is one of the red algae species with bioactive as an anti-aging and antioxidant compound. This study aims to synthesize, characterize and determine the antioxidant activity of F. Vesiculosus nanoparticles compounds. Characterization for nanoparticle compounds is Scanning Electron Microscope (SEM), Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), and Particle Size Analyzer (PSA). The antioxidant activity test used the DPPH method. The results of the SEM characterization of nanoparticles showed the results of the formation of spherical particle surfaces known as a spherical formation. SEM-EDX shows several constituent elements of silver nanoparticles F. vesiculosus, namely C, O, Na, Mg, Cl, and K. Characterization silver nanoparticles using PSA measuring the particle size are 74.06 nm at 99.5% distribution. Characterization of silver nanoparticles using XRD showed crystalline character. The FTIR pattern shows the functional groups of alkenes, aromatic rings, ethers, amines/amides, alkenes, and alkanes. The antioxidant test results showed that the inhibition concentration for ascorbic acid was 1.13 ppm, silver nanoparticles F. vesiculosus 177.6 ppm, F. vesiculosus crude extract 1335 ppm, and respectively, ascorbic acid > silver NP > crude extract F. vesiculosus. The test results show that the antioxidant activity of the nanoparticle compounds increased from the very weak into the strong category.  Keywords: antioxidant activity, Fucus vesiculosus, Nanoparticle.